The Phenomenon of Religious Misinformation and the Challenges of Authority in the Artificial Intelligence Ecosystem - Sari, Nurin Kartika; Fasya, Zaini (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2026)
The rapid development of Artificial Intelligence (AI) has transformed the way society accesses and understands religious information through social media, search engines, and AI-based chatbots. This condition creates challenges related to religious misinformation, algorithmic bias, and the shift of religious authority from traditional scholars to digital platforms. This study aims to analyze the characteristics of religious misinformation in the AI ecosystem, examine the crisis of religious authority, and formulate a religious moderation strategy based on digital literacy. The research employed a qualitative descriptive method with a library research approach. Data were collected from scientific journals, books, reports, and recent studies related to AI, digital religion, and religious moderation. Data analysis used critical and interpretative content analysis through data reduction, categorization, interpretation, and conclusion drawing. The findings reveal that AI algorithms contribute to filter bubbles, echo chambers, fragmented religious understanding, and AI hallucination in religious discourse. Digital popularity increasingly replaces sanad-based authority and creates algorithmic authority in religious practices. Religious moderation based on wasathiyah values and digital tabayyun literacy becomes an important strategy to mitigate radicalization and misinformation in digital spaces. AI should function as an educational assistant, while moral and theological authority remains centered on scholars and religious institutions.